PERAN PENDIDIKAN AGAMA ISLAM DALAM MENING-KATKAN KESADARAN DI LINGKUNGAN SMA SWASTA BUDI AGUNG MEDAN MARELAN PADA SISWA KELAS XI USMAN BIN AFFAN IPA TAHFIDZ - Azzahra, Diva Nafisah; Siregar, Syifa Habibah; Siregar, Ummu Habibah (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine the role of Islamic religious education in increasing environmental awareness at Budi Agung Medan Marelan Private High School for Class XI Usman Bin Affan Ipa Tahfidz students. This research uses a qualitative method to collect data and then describe the results obtained from existing facts. The data analysis technique that the researcher uses is to reprocess the reading material that the researcher has collected as well as the results of interviews that the researcher has evaluated and produce information based on the results of observations. The role of Islamic religious education is very religious because it is very important and is always applied in the school environment. In particular, religious activities and lecture methods are also always used in class or outside the classroom. Because this role is very important as a foundation in forming students' character at school